Sodium ion incorporated alumina - A versatile anisotropic ceramic. Issue 15 (December 2019) - Pujar, Pavan; Gupta, Bikesh; Sengupta, Pradyut; Gupta, Dipti; Mandal, Saumen
Abstract: The present article is a review of crystal structure dependent anisotropic properties of β and β″-phases of sodium ion incorporated alumina. The anisotropy in electrical properties such as ionic conductivity and dielectric permittivity is due to the layered structure. Conducting plane between two consecutive spinel aluminas constituting loosely bound mobile sodium ions, promote ionic conductivity in the parallel direction. In contrary, the restricted movement of ions in the orthogonal direction brings about polarization giving it directional dielectric property. High ionic conductivity of 1.3 S/cm and large dielectric constant of ˜ 200 are reported. Exchanging sodium ions with different cations, such as potassium and lithium, results in similar anisotropy. The processing of β and β″-phases along with metastability of intermediate mullite phase is described in the current review. In addition, the applications of sodium ion incorporated aluminas, such as solid electrolyte in batteries, thin film transistors and gas sensors are discussed.